Black Women’s Writing
X, 189 p.
Keywords: This book contains a lively and wide ranging collection of critical essays on Black women's writing from Afro-American, African, South African, British and Caribbean novelists, poets, short story writers and a dramatist. The contributors are black and white, female and male, academics and readers who chart their engagement with and enjoyment of the texts of some of the key figures in black women's writing across several continents.